The Rationality to Use of Galectin-3 as Target in Biomarker-Guided Therapy of Type 2 Diabetes Mellitus - Berezin, A. E.; Березін, Олександр Євгенійович (My University, 2016)
Galectin-3 is a multifunctional chimaera-type β-galactoside binding protein that has been linked to incident Cardiovascular (CV) and renal disease, fibrosis and tissue injury. Elevated level of serum galectin-3 was found in patients with Type 2 Diabetes Mellitus (T2DM) and associate well with CV complications. The short commentary depicts the role of galectin-3 in risk stratification in T2DM individuals. Although perspectives of clinical implementation of galectin-3-guided therapy in T2DM patients are widely discussed, there is evidence regarding cyto-protective role of galectin-3 in diabetes. Whether is rationale to achieve full control under serum galectin-3 as a predictor of successful T2DM treatment is not clear. Further investigations are needed to explain the role of galectin-3 in T2DM development and progression.
Keywords: Diabetes mellitus; Biomarkers; Galectin-3; Risk stratification; Targeting for therapy